Temporomandibular Myofacial Pain Treated with Botulinum Toxin Injection - Niv Mor; Christropher Tang; Andrew Blitzer (Toxins, 2015)
This article reviews the diagnoses and treatment of temporomandibular disorders (TMD) and outlines of the role of botulinum toxin (BoNT) in the treatment of myofacial TMD. This manuscript includes a brief history of the use of BoNT in the treatment of pain, the mechanism of action of BoNT, and the techniques for injections, adverse effects and contraindications when using BoNT to treat mayofacial pain caused by TMD.